P808 Risk of relapse after vedolizumab withdrawal in Inflammatory Bowel Disease for patients in histological remission. (30th January 2023) - Blad, W; Whitley, L; Harrow, P
Abstract: Background: A key clinical question is whether we should be withdrawing advanced inflammatory bowel disease (IBD) medications after a period of sustained remission. There is data to suggest that risk of relapse on withdrawal of vedolizumab is higher than that of anti-TNF therapy 1 . Drug costs are still considerable and so withdrawal of medications will also have significant financial benefits. The aim was to review the outcomes of vedolizumab withdrawal in patients in remission, in particular for those where a clinical decision was made following confirmed histological remission of their IBD Methods: This was a single-centre retrospective review of patients in the IBD clinic at a tertiary referral centre in London. We analysed all those who had stopped vedolizumab at least six months prior and were in either clinical, biochemical, radiological, endoscopic or histological remission. We assessed for evidence of a flare of disease following withdrawal of vedolizumab and the need of further biological treatment. Results: 38 patients had vedolizumab withdrawal for remission with a median length of treatment of 36 months. 28 (74%) had a flare up of disease requiring medication change with 24 (63%) requiring biologics. 21 restarted vedolizumab and 79% responded to this medication. Importantly, 5 patients are still less than a year since stopping and so still at high risk of relapse. Of the 21 patients confirmed to be in histological remission, 17 (81%) had a flare of disease requiring further treatment, of which 15 (71%) required biologics. Median time to flare was 7 months with only two patients flaring after a year of cessation. All 15 were started on vedolizumab and 12 (80%) responded to this but one had a subsequent early secondary loss of response. Of those who did not respond to vedolizumab, one required emergency surgery, one responded to ustekinumab and one only has partial response to a third biologic. Conclusion: Relapse following vedolizumab withdrawal occurs in a significant number of patients even when they have been in remission for a long period of time. It usually occurs quickly within the first year and having confirmed histological remission does not seem influence this risk. Recapture of response is reasonably good and occurs in four fifths of patients. Despite the significant cost savings of stopping vedolizumab, clinicians need to consider the risk to benefit ratio of stopping when relapse is such a common event. 1 Martin, A., Nachury, M., Peyrin-Biroulet, L., et al, GETAID-Vedo-STOP Study Group (2020). Maintenance of Remission Among Patients With Inflammatory Bowel Disease After Vedolizumab Discontinuation: A Multicentre Cohort Study. Journal of Crohn's & colitis, 14 (7), 896–903. https://doi.org/10.1093/ecco-jcc/jjaa005